1997
DOI: 10.1042/bj3250751
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of a distal (3′-phosphate) group of CoA in the recombinant human liver medium-chain acyl-CoA dehydrogenase-catalysed reaction

Abstract: The X-ray crystallographic structure of medium-chain acyl-CoA dehydrogenase (MCAD)-octenoyl-CoA complex reveals that the 3h-phosphate group of CoA is confined to the exterior of the protein structure [approx. 15 A H (1.5 nm) away from the enzyme active site], and is fully exposed to the outside solvent environment. To ascertain whether such a distal (3h-phosphate) fragment of CoA plays any significant role in the enzyme catalysis, we investigated the recombinant human liver MCAD (HMCAD)-catalysed reaction by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The majority of the substrate-binding energy comes from the CoA moiety of the substrate that is not directly involved in any of the chemical steps, as seen with 3-oxoacid CoA-transferase (41). It has been shown that 3′phosphate group of CoA moiety contributes 5.2 kJ/mol in the binding free energy with human MCAD (42). Also, the K m of glutaryl-patetheine is some 590-fold higher than glutaryl-CoA reflecting the contribution of the 3′-phospho-5′ADP moiety of the CoA thiolester substrate in the binding process (13).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the substrate-binding energy comes from the CoA moiety of the substrate that is not directly involved in any of the chemical steps, as seen with 3-oxoacid CoA-transferase (41). It has been shown that 3′phosphate group of CoA moiety contributes 5.2 kJ/mol in the binding free energy with human MCAD (42). Also, the K m of glutaryl-patetheine is some 590-fold higher than glutaryl-CoA reflecting the contribution of the 3′-phospho-5′ADP moiety of the CoA thiolester substrate in the binding process (13).…”
Section: Resultsmentioning
confidence: 99%
“…Several acyl-dephospho-CoAs have been synthesized in vitro ( 26,27 ), and valproyl-dephospho-CoA has been identifi ed in isolated rat liver mitochondria from CoA trapping reagent (valproate), suggesting that both the phosphoand dephospho-CoA forms are biologically active ( 28 ). The absence of the 3 ′ -phosphate group on the ribose moiety of acyl-dephospho-CoAs is the only difference compared with their corresponding acyl-CoAs.…”
Section: Lc-ms/ms Is the Most Sensitive Methods To Analyze Acylcoas Anmentioning
confidence: 99%
“…7 A). It has been demonstrated that the 3′-phosphate group of acyl-CoA plays a significant role in human medium-chain acyl-CoA dehydrogenase 45 , 46 . In this case, the 3′-phosphate group makes an enthalpic contribution derived from van der Waals interactions between the 3′-phosphate group and the surrounding protein moiety.…”
Section: Discussionmentioning
confidence: 99%